Pemuridan Kontekstual sebagai Strategi Pendidikan Kristen di Masyarakat Multikultural - Immanuela Deru; Indriati TjiptoPurnomo; Joshua Christian Wenas; Simon Simare-mare (Sekolah Tinggi Teologia Kerusso Indonesia, 2026)
This study examines contextual discipleship as a strategic approach to Christian education in a multicultural society. It employs a convergent mixed-methods design to obtain a comprehensive understanding of how discipleship contributes to students’ spiritual growth and character formation. Quantitative data were gathered through structured questionnaires, while qualitative data were collected through in-depth interviews and focus group discussions with relevant participants. The findings show that contextual discipleship significantly strengthens students’ understanding of faith, promotes tolerance and respect for diversity, encourages social engagement, and helps students respond wisely to challenges arising from technological development and digital culture. Contextual discipleship becomes effective when it is implemented consistently, supported by relational mentoring, and grounded in the translation of Gospel values into the learners’ real-life social context. The study concludes that contextual discipleship is a strategic and transformative model for developing holistic Christian education that is spiritually formative, socially responsive, and relevant to multicultural realities. Therefore, this approach can strengthen Christian educational practice and equip learners to live faithfully, responsibly, and constructively within diverse contemporary communities amid ongoing social, cultural, and increasingly digital transformation today.